Impact of Rifaximin Therapy on Ischemia/Reperfusion Injury in Liver Transplantation: A Propensity Score–Matched Analysis. Issue 12 (4th November 2019) - Ito, Takahiro; Nakamura, Kojiro; Kageyama, Shoichi; Korayem, Islam M.; Hirao, Hirofumi; Kadono, Kentaro; Aziz, Justine; Younan, Stephanie; DiNorcia, Joseph; Agopian, Vatche G.; Yersiz, Hasan; Farmer, Douglas G.; et al.
Abstract : Intestinal microbiota is thought to play an important role in hepatic ischemia/reperfusion injury (IRI) after liver transplantation (LT). Rifaximin, a nonabsorbable antibiotic used to treat encephalopathy, exhibits antibacterial activity within the gut. We report the first study examining the impact of pre‐LT rifaximin use on reducing hepatic IRI and inflammatory cell infiltration after LT. This retrospective single‐center study included adult LT recipients from January 2013 through June 2016. Patients were divided into 2 groups based on duration of rifaximin use before LT: rifaximin group (≥28 days) and control group (none or <28 days). Patients receiving other antibiotics within 28 days of LT and re‐LTs were excluded. Outcomes and messenger RNA (mRNA) expression in the graft were compared by 1:1 propensity score–matching and multivariate analyses. On 1:1 matching (n = 39/group), rifaximin patients had lower postoperative serum transaminase levels and lower early allograft dysfunction (EAD; 10.3% versus 33.3%; P = 0.014). Of the matched patients, 8 patients (n = 4/group) had postreperfusion liver biopsies (approximately 2 hours after reperfusion) available for mRNA analysis. Hepatic expression of CD86 (macrophage marker) and cathepsin G (neutrophil marker) was significantly lower in rifaximin patients than controls ( P < 0.05). The multivariate analysis included 458 patients. Rifaximin treatment <28 days was identified as an independent risk factor EAD in all patients and those with high Model for End‐Stage Liver Disease (MELD) score (MELD ≥35; n = 230). In conclusion, the propensity score–matched and multivariate analyses suggest a therapeutic role of rifaximin in reducing EAD. Pre‐LT rifaximin administration exerted a protective function against early liver injury, potentially by suppressing inflammatory cell activation in the graft.